Homologous ELISA for detection of oligomeric human TNF: properties of the assay - Petyovka, Natalia; Lyach, Lyudmila; Voitenok, Nikolai N. (Journal of immunological methods, 1995)
In order to quantify oligomeric human tumor necrosis factor-α (TNF), we have developed a sensitive homologous enzyme-linked immunosorbent assay (Hm-ELISA) using the same monoclonal antibody (MoAb) for both solid and liquid phase. Different anti-TNF MoAb have been compared in terms of their efficacy in the Hm-ELISA, affinity, neutralization capacity and epitope specificity. The data suggest, that effectiveness in the Hm-ELISA may represent a novel characteristic of MoAb. Of the MoAbs tested, 5 N was capable of recognizing oligomeric TNF in the Hm-ELISA with a detection limit of 15 pg/ml. Furthermore, using Hm-ELISA against human TNF, interleukin-8 (IL-8) and lymphotoxin, we have demonstrated that these cytokines are oligomeric in physiological solutions, but are converted into monomeric forms in the presence of the non-ionic detergent Tween 20. High salt buffer was employed to abrogate a nonspecific false positive reaction in the Hm-ELISA found in nearly half of the plasma samples obtained from healthy subjects. Finally, a good correlation between the Hm-ELISA and the L929 bioassay was observed for natural and recombinant TNF measured in human plasma.